Characterization of coffee (Coffea arabica) husk lignin and degradation products obtained after oxygen and alkali addition. (June 2018) - de Carvalho Oliveira, Fernanda; Srinivas, Keerthi; Helms, Gregory L.; Isern, Nancy G.; Cort, John R.; Gonçalves, Adilson Roberto; Ahring, Birgitte Kiær
Graphical abstract: Highlights: Acid and alkaline pretreatments of coffee husk resulted in 92% pure lignin. Lignin was mainly H-type and β-O-4 structures constituted the main inter-unit bonds. Alkaline wet oxidation of the lignin showed greater conversion to organic acids. Aromatic aldehyde yield was highest at 11.7 wt% NaOH and temperatures over 210 °C. Abstract: The full use of biomass in future biorefineries has stimulated studies on utilization of lignin from agricultural crops, such as coffee husk, a major residue from coffee processing. This study focuses on characterizing the lignin obtained from coffee husk and its further wet oxidation products as a function of alkali loading, temperature and residence time. The lignin fraction after diluted acid and alkali pretreatments is composed primarily of p -hydroxylphenyl units (≥49%), with fewer guaiacyl and syringyl units. Linkages appear to be mainly β-O-4 ether linkages. Thermal degradation of pretreated lignin during wet oxidation occurred in two stages. Carboxylic acids were the main degradation product. Due to the condensed structure of this lignin, relatively low yields of aromatic aldehydes were achieved, except with temperatures over 210 °C, 5 min residence time and 11.7 wt% NaOH. Optimization of the pretreatment and oxidation parameters are important to maximizing yield of high-value bioproducts from lignin.